COSTING MODALITIES IN CONSUMPTION OF RESOURCES: A CASE STUDY OF ABC IN BANKS - Bezerra, Francisco Antonio (2008)
With the incitement in competition and motivated by the changes in objectives of cost information systems, service companies have become obliged to develop or, under the best of hypotheses, re-design their systems of costing. As a function of its characteristics in the allocation of indirect costs, the ABC methodology has been used in dealing with this type of information in service companies. Costing based on activities (Activity-Based Costing – ABC) can be useful in determining and evaluating a company’s cost structure, assisting in decisions that permit the establishment of sustainable competitive advantages. This article describes an example of how cost information systems based on activities can be used by service companies, especially in financial institutions, to set costs of the different forms of consumption of resources imposed by clients, referred to in this article as Cost Modalities. The study can be classified as exploratory research, with a quantitative approach, realized in a real world situation in a financial institution. Keywords: Activity-Based Costing. Cost management. Management of Bank processes. Cost of clients.